PENERAPAN MODEL PEMBELAJARAN JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS XI SMA NEGERI 1 PEMATANG BANDAR - Tri Anggraini, Sarah; Damanik, Risjunardi; Mustika Piliang, Fenny (Program Studi Pendidikan Biologi, Fakultas Keguruan Dan Ilmu Pendidikan Universitas Simalungun, 2023)
Application of the Jigsaw Learning Model to Improve Biology Learning Outcomes on the Human Excretory System in Class XI Science 1 and Science 2 of SMA Negeri 1 Pematang Bandar, Pematang Bandar District, Simalungun Regency. The purpose of this study was to improve the learning outcomes of class XI students of SMA Negeri 1 Pematang Bandar in the 2021/2022 academic year using Jigsaw learning. The subjects of this study were 30 class XI Science 1 and Science 2 students of SMA Negeri 1 Pematang Bandar, Pematang Bandar District, Simalungun Regency, in the 2021/2022 academic year. This study used a qualitative descriptive approach with Classroom Action Research (CAR) type which was implemented for one month, from March to April, in two cycles. Each cycle consisted of four stages: planning, action, observation, and reflection. The data collection techniques used in this study are (1) Participant observation method because the teacher as a researcher also observes and is observed directly by collaborators who also observe the activeness of teachers and students during the learning process. (2) Documentation method, used to determine the initial abilities of students and to obtain data about SMA Negeri 1 Pematang Bandar, Pematang Bandar District, Simalungun Regency which includes history, geographical location, and also about its vision and mission, (3) Test method is used to determine student learning outcomes after working on the questions given at the end of learning in each cycle. The conclusion of the study is that the application of the Jigsaw learning model can improve student activity and learning outcomes in biology learning in class XI SMA Negeri 1 Pematang Bandar in the 2021/2022 Academic Year. This can be seen in the results of the analysis of learning outcome data in each cycle which has increased. Cycle I with a class average of 69.7%, student absorption of 73.7%, and student learning completeness of 70%. Meanwhile, the results of the second cycle test showed an average score of 80.4%, an absorption rate of 78.8%, and a student learning achievement of 90%. Based on the data above, this research is very useful for improving teacher competency in developing students' knowledge about the excretory system at school. The application of the Jigsaw learning model can also improve the quality of the learning process about the excretory system for students, thereby improving the quality of teacher and student activities.